Perancangan Analisa Risiko ISO 9001:2015 Pada PT Berkah Utama Alloy - Permadi, Rico (Jurnal Titra, 2019)
This Paper is describe about design of risk management on PT Berkah Utama Alloy. There is two section, first was risk identification and second was risk mitigation. There is six thing we need to know to risk identification it was risk potential, risk impact, risk cause, frequency value, impact value, and company doing right now. Risk mitigation was design to control to minimize the risk. There is four kind of mitigate that was risk transfer, administration control, technical control, reduce control, and retention control. Mitigate risiko was design for feuture and the have an objective to reduce or disepear risk value in process and key performance indicator medium and heavy. In this thesis there is 16 risk identification and 11 risk mitigate, whom seven was heavy and the rest was medium. In seven heavy risk two of them suggested to change their work procedure for Department Puechasing and Research and Development